SEBUAH TINJAUAN TENTANG PARASIT TALI PUTRI (Cuscuta spp.) DAN PENGENDALIANNYA - Sunaryo Sunaryo (BERITA BIOLOGI, 2003)
Cuscuta species are parasitic seed plants with twining stems, that coil and fasten to host plants with attachments called haustoria.The Cuscuta stem forms the haustorial coil around the host.Several species of Cuscuta are troublesome parasites on numerous dicotyledonous plants and make eradication and control most difficult. Overall control of Cuscuta is based on mechanical, cultural,chemical and biological methods. Resistant varieties of susceptible crops and biological control are presently of limited importance.Chlorpropham, DCPA, Dichlobenil, and CDEC are soil-applied herbicides that have been used to control Cuscuta in various crops for many years. Nevertheless, integrated control of Cuscula is still considered to be more important.